A study on prostaglandin E1 therapy in critical limb ischaemia patients to evaluate the improvement in vascularity - Kurien, John S.; E. U., Sansho; Varghese, Sandeep; Jose, Toney (International Surgery Journal, 2017)
Background: Diffuse peripheral arterial disease or peripheral occlusive vascular disease (POVD) involving the lower limb is a debilitating illness with high incidence of morbidity and mortality. The objective of this study was to assess the improvement of ulcer healing and improvement of the level of amputation in patients with diffuse peripheral arterial disease after administration of prostaglandin E1. Methods: From June 2013 to November 2014, a total of 45 patients having critical limb ischaemia (Fontaine’s grade III and IV) not suitable for angioplasty and stenting or bypass procedures received different courses of Prostaglandin E1 (PGE1). 20 patients (44.44%) received 6 full courses of PGE1, 3 patients (6.66%) received 5 courses, 5 patients (11.11%) received 4 courses, 4 patients (8.8%) received 3 courses, 4 patients (8.8%) received 2 courses and 9 patients (20%) received one course. PGE1 was administered through intravenous infusion (Alprastodil 100mcg) over 10 hours a day for 5 days in one month (1course). They were followed up for 3 years till June 2017.The improvement in level of amputation, ulcer healing and complications were assessed. Results: 14 patients (31.1%) did not require amputation of limbs/ toes, 24 patients (53.3%) have the same amputated status while 7 patients (15.6%) required higher amputation. This study justifies the role of PGE1 therapy in improving the peripheral arterial pulsations and thereby augmenting ulcer healing and improving the level of amputation. Conclusions: After diagnosing a patient with advanced CLI where angioplasty and stenting or bypass procedures are not possible, aggressive treatment for the non-healing ulcer, amputation of gangrenous limbs or toes and starting the PGE1 therapy early not only arrest the progression of POVD but even reverses it to some extent.